PREVENTING THE OBLITERATION OF ARTIFICIAL ANASTOMOSIS AFTER INTRANASAL FRONTOTOMY IN PATIENTS WITH CHRONIC FRONTAL SINUSITIS - A.V. Loburets; S.B. Bezshapochnyi (Проблеми екології та медицини)
In most cases, chronic forms of sinusitis require the use of surgical treatments. The analysis of data in the world literature shows that the recurrence after endoscopic sinusitis functional sinusotomy is about 20%, and in almost half of cases it is required to conduct reintervention. The aim of the research: To study the effectiveness of plastic reconstruction of frontal-nasal anastomosis using muco-periosteal flap on the leg during intranasal frontotomy in patients with chronic frontal sinusitis. Materials and methods. In the period from January 2014 to January 2017 at the ENT department of Poltava M.V. Sklifosovskii Regional Clinical Hospital, surgical treatment of 248 patients with chronic inflammation of the frontal sinus was conducted. The study included 67 patients with uncomplicated course of chronic sinusitis. These patients were divided into 2 groups: Group 1 – 31 patients that were operated using the classical method of intranasal frontotomy, by extended drainage type (Draf II), Group 2 – 36 patients operated using the modified method. In order to prevent fusion of the formed artificial fronto-nasal anastomosis in endonasal access and to obtain stable functional results, we have used the modified method of intranasal frontotomy. Research results. Indicators of rhinomanometry before surgery and in 1 month display a statistically significant difference in patients of Group 2, who underwent nasal frontotomy with correction of INS (p <0.05). Conclusions: 1. In all patients of ENT Department, isolated or combined chronic inflammation of frontal sinus in general structure of sinusitis was observed in 21.64% of cases. 2. Chronic inflammation of frontal sinus requires the use of surgical management in 95% of cases. 3. The application of plastic reconstruction of frontal-nasal anastomosis during intranasal frontotomy promotes earlier clinical convalescence of patients, reduces the number of relapses of frontal sinusitis. 4. The application of rhinomanometry allows us to give qualitative and quantitative characteristics of the status of nasal ventilation, which is an important criterion for the effectiveness of the correction of INS structures and prognostic indicator of PNS ventilation.